The Influence Of Family Environment, Entrepreneurship Training And Motivation On Student Enterprise Interest: (Case study of student in Management Program at Serang Raya University) - Hamdan Hamdan (International Journal of Management Research and Economics, 2025)
This research is motivated by the influence of the family environment, entrepreneurship training and motivation on students' interest in entrepreneurship. The purpose of this research is to find out whether the family environment, entrepreneurship training and motivation influence the interest in entrepreneurship. This research was conducted at Serang Raya University which is located on Jalan Raya Serang-Cilegon KM 05 Serang-Banten. The population in this study were students of the Management Study Program, Faculty of Economics who had taken Entrepreneurship courses with a sample of 270 respondents. Sampling using purposive sampling technique. Research data collection techniques were carried out through questionnaires. The data analysis technique uses multiple regression analysis techniques. The results showed that the family environment, entrepreneurship training and motivation influenced the interest in entrepreneurship at Serang Raya University students. Recommendations for further research update other variables and research objects.